Anticonvulsant and anxiolytic activities of methanol extract of Securidaca longipedunculata Fres. root bark in mice - Hyellavala Joseph Fomnya, Saidu Ibrahim Ngulde, Sanni Saka, Sarah Malgwi Gana, Bukar Umaru, Mohammed Shuaibu Auwal (Journal of Applied Pharmaceutical Science, 2023)
Securidaca longipedunculata (SL) is an extensively utilized medicinal plant in folk medicine. Pentylenetetrazole- (PTZ-)induced seizures and strychnine-induced convulsions were used for evaluating the anticonvulsant activities, while open field test (OFT) and elevated plus maze (EPM) were used to evaluate the anxiolytic activities. In each of these tests, both sexes of mice were selected randomly and divided into five different groups comprising five mice per group. The first group received normal saline 0.1 ml/10 g (negative control) and the next three groups received methanol extract of the plant root bark at 0.5, 1.0, and 1.5 mg/kg, respectively, while the last group received diazepam 1.0 mg/kg (positive control) intraperitoneally. The extract showed anticonvulsant activity at 1.0 and 1.5 mg/kg by significantly (p < 0.05) delaying the onset of convulsion and shortening the duration of convulsion in PTZ-induced seizures. In the strychnine-induced convulsion, there was a significant delay in the onset of the convulsion but not in the duration. The extract also exhibited anxiolytic activities at 1.0 and 1.5 mg/ kg by significantly (p < 0.05) increasing the time taken within the central zone as well as the number of entries to the center zone of the field in OFT, while in the EPM, there was an increase in the time taken at the open arm and in the frequency of entries into the open arm. Diazepam as the positive control recorded better anticonvulsant and anxiolytic activities compared to the extract. The result proved that the methanol extract of SL root bark possesses dose-dependent anticonvulsant and anxiolytic activities, and a potent anticonvulsant/anxiolytic agent could be developed from the extract.
Keywords: Securidaca longipedunculata, anticonvulsant, anxiolytic, EPM, OFT